The Relationship Between Gender, Age, and Social Support Factors and Self-Efficacy in Laboratory Practicum Learning Among Nursing Students - Nunik Purwanti; Hasina, Siti Nur; Nabila Ainun Maghfiroh; Andikawati Fitriasari (Journal for Quality in Public Health, 2025)
The influence of self-efficacy on behavior is significant in mastering situations to accomplish desired objectives. The objective of this research was to determine and investigate the connection between the variables of gender, age, and social support and their impact on self-efficacy in practical laboratory settings within nursing education. A cross-sectional survey among the undergraduate nursing students was conducted in the class of 2022 at a private university in Surabaya, those who participated in the infusion practicum in the laboratory. The population consists of 169 students, with a sample of 63 respondents selected using a random probability sampling technique. Gender, age, and social support are independent variables, with self-efficacy as the dependent variable. The MSPSS (Multidimensional Scale of Perceived Social Support) and GSES (General Self-Efficacy Scale) were the research instruments. Data analysis was conducted using chi-square and Spearman rank tests with a significance threshold of less than 0.05. This study found no significant correlation between gender and self-efficacy in nursing students (0.888), no significant correlation between age and self-efficacy in nursing students (0.212), but a significant correlation between social support and self-efficacy in nursing students (0.000). Nursing education institutions are urged to enhance social support initiatives within the learning environment, encompassing mentoring, peer support, and family participation.